A comprehensive review on the chemical constituents and pharmacological activities of Mustard plants (Jahangirnagar University Journal of Biological Sciences, 2024)
Medicinal plants are used worldwide to combat and treat various deadly diseases. Among them, mustard plants (Brassica campestris and B. nigra) are two very common plants of medicinal value in the Asia region. These plans are used to treat neuralgia, spasms, snakebite, alopecia, epilepsy, toothache, etc. They also have some history of spiritual usage. According to various scientific studies B. campestris and B. nigra possess anticancer, antioxidant, and antibacterial activity, antiepileptic effect, antidiabetic effect, neuroprotective effect, antifungal and, anti-obesity activities, etc. Glucosinolates, polyphenols, condensed tannins, vitamins, palmitic, oleic and linolenic acids, etc. were isolated from these plants. This study makes a comprehensive review of different aspects of these plants including their description, uses, chemical constituents, pharmacological activities, with a special focus on their anti-cancer activity, adverse effects and contraindications. The chemical constituents responsible for their anticancer activity have also been highlighted. The review also covered anti-nutritional property of the plants.Jahangirnagar University J. Biol. Sci. 12(1 & 2): 107-125, 2023 (June & December)